A Cluster-Randomized Trial of Restorative Practices: An Illustration to Spur High-Quality Research and Evaluation. Issue 4 (1st October 2016) - Acosta, Joie D.; Chinman, Matthew; Ebener, Patricia; Phillips, Andrea; Xenakis, Lea; Malone, Patrick S.
ABSTRACT: Restorative practices in schools lack rigorous evaluation studies. As an example of rigorous school-based research, this article describes the first randomized control trial of restorative practices to date, the Study of Restorative Practices. It is a 5-year, cluster-randomized controlled trial (RCT) of the Restorative Practices Intervention (RPI) in 14 middle schools in Maine to assess whether RPI affects both positive developmental outcomes and problem behaviors and whether the effects persist during the transition from middle to high school. The 2-year RPI began in the 2014–2015 school year. The study's rationale and theoretical concerns are discussed along with methodological concerns including teacher professional development. The theoretical rationale and description of the methods from this study may be useful to others conducting rigorous research and evaluation in this area.